Effects of the crystallinity of fluoropolymer binders components in polymer-bonded explosives on shock Hugoniots: A computational study - Wen-yu Zhou; Hua-rong Li; Yong Han; Liu Liu; Hong Yang; Yang Zhou (Energetic Materials Frontiers)
Fluoropolymers play a crucial role as binders in polymer-bonded explosive (PBX) formulations. However, there is a lack of clear understanding of the effects of increased fluoropolymer crystallinity on the shock response of PBXs in the service environment. This study investigated the shock Hugoniots of two widely applied fluoropolymer binders: (1) F2314 from China—a copolymer with a molar ratio of vinylidene fluoride (VDF) to chlorotrifluoroethylene (CTFE) of 1:4 and (2) F2313 from the United States, also known as Kel F-800, with a VDF to CTFE molar ratio of 1:3. The Hugoniot curves of both fluoropolymers were calculated based on equilibrium molecular dynamics (MD) and a mixing rule. Furthermore, the corresponding P–V curves were obtained through fitting using the Tait equation of state (EOS). Their calculated parameters, including zero-pressure bulk modulus (κo) and sound velocity (co), agreed well with experimental data. The results reveal that the Hugoniots of amorphous F2314 and F2313 exhibited negligible differences. However, increasing crystallinity significantly impacted the Hugoniot curves of both fluoropolymers, especially for F2314 with high crystallinity. The obtained macroscopic characteristic parameters, namely κo and co, exhibited an exponential dependence on crystallinity. Physically, this phenomenon can be attributed to a reduction in the compressible free volume of the fluoropolymers due to a more orderly chain arrangement. Additionally, under the same compression ratio, the shock temperature of the fluoropolymers increased with the crystallinity, posing potential safety risks to explosives. These findings establish a correlation between the crystallinity of fluoropolymers and the shock properties of PBXs, providing a theoretical reference for the formulation design of fluoropolymer-based PBXs.